Biaxial proximal interphalangeal joint hyperflexions in a five‐year‐old Holstein bull. Issue 2 (20th June 2019) - Mulon, Pierre‐Yves; Snowden, Robert T; Videla, Ricardo; Anderson, David E
Abstract : A five‐year‐old Holstein bull became lame after dismount during semen collection. Swelling of the pastern of the left front limb was noted. Radiographic images showed biaxial hyperflexion of the proximal interphalangeal joints in digits III/IV without hyperextension of the metacarpophalangeal joint. Conservative management (stall confinement and NSAIDs) failed to resolve the lameness. External coaptation to stabilise the joint failed to prevent hyperflexion of the joint within the cast and to improve comfort. Pressure sores developed after seven days. Surgical arthrodesis of the PIP joint was performed on each digit by application of a locking compression plate. The bull healed and arthrodesis of the joints progressed over the next 16 weeks. At that time, the bull was walking sound and was returned to semen collection. One year after surgery, the attending veterinarian reported that the bull remained sound at a walk and was still being used for semen collection.